Dilema Code Is Law: Analisis Keadilan Kontraktual dan Perlindungan Hukum Bagi Pihak Lemah dalam Smart Contract - Candra Wijaya Muling; Raul Gindo Cahayo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of blockchain technology has given rise to smart contracts as agreements that are executed automatically without human intervention, embodying the concept of code is law, which positions computer code as the highest authority in determining the rights and obligations of the contracting parties. This concept has the potential to conflict with the principles of contractual justice in conventional civil law, particularly the principles of good faith, contractual balance, and the protection of weaker parties. This study employs a normative legal research method to analyze the validity of smart contracts within the framework of Article 1320 of the Indonesian Civil Code (Kitab Undang-Undang Hukum Perdata), evaluate the limits of legal liability arising from technical failures in automated execution, and formulate a legal protection framework for weaker parties. The findings indicate that the element of consent in smart contracts is reduced to technical assent, which does not fully represent a genuine meeting of the minds, while the requirement of a lawful cause is vulnerable to being obscured by the complexity of code that is not transparent to ordinary users. The study further finds that technical failures, such as software bugs or algorithmic errors, cannot automatically be classified as force majeure. Instead, such failures must be assessed based on the principles of due care and foreseeability on the part of the system developer. Consequently, in many cases, they are more appropriately characterized as a breach of contract resulting from negligent system design.